The role of endoscopic ultrasound guided fine needle aspiration (EUS-FNA) in non small cell lung cancer (NSCLC) patients: SEED-SEPD-AEG Joint Guideline - Enrique Vázquez-Sequeiros; Fernando González-Panizo Tamargo; Ángel Barturen; Ángel Calderón; José Miguel Esteban; Gloria Fernández-Esparrach; Antonio Gimeno-García; Angels Ginés; José Lariño; Mercedes Pérez-Carreras; Rafael Romero; José Carlos Subtil; et al. (Revista Espanola de Enfermedades Digestivas, 2013)
Lung cancer is one of the most frequent neoplasms in our environment, and represents the first cause of cancer related death in western countries. Diagnostic and therapeutic approach to these patients may be complicated, with endoscopic ultrasound guided fine needle aspiration (EUS-FNA), classically performed by gastroenterologists, playing a very important role. As this disease is not closely related to the "digestive tract", gastroenterologists have been forced to update their knowledge on this field o adequately diagnose this significant group of patients. The recent advent of modern and promising techniques like endobronchial ultrasound guided fine needle aspiration (EBUS-FNA) have prompted new approaches for diagnosis and staging of this type of patients. In this clinical guideline, the "Sociedad Española de Endoscopia Digestiva" (SEED), "Sociedad Española de Patología Digestiva" (SEPD) and the "Asociación Española de Gastroenterología", have jointed efforts to update the existing knowledge on the field and provide their members with evidence based recommendations.